Planet earth calling: unveiling the brain’s response to awe and driving eco-friendly consumption - Yin, Meiling; Lee, Eun-Ju (Frontiers in Neuroscience, 2023)
Eco-friendly consumption is important for solving climate crisis and moving humanity towards a better future. However, few consumers are willing to pay premiums for eco-friendly products. We investigated the psychological and neural factors that can increase eco-friendly consumption. We propose an experience of awe, in which the individual self is temporarily attenuated as the importance of beings other than oneself increases. Behavioural (Study 1) and functional magnetic resonance imaging (fMRI) (Study 2) experiments were conducted to explore the awe mechanisms through which climate crisis messages lead to eco-friendly consumption. In Study 1, we found participants felt awe when exposed to climate crisis messages, and their choice of eco-friendly consumption increased. In Study 2, we found that, when individuals were exposed to messages depicting the climate crisis (as opposed to a control stimulus), their brains exhibited a lower level of activation in the self-awareness processing and a higher level of activation in external attention processing areas. These results suggest that the awe experience plays an important role in promoting eco-friendly consumption. Marketing must evolve from satisfying basic individual needs to a high level for the well-being of humanity, the planet, and the biosphere. This study sheds light on our understanding of human perceptions of the climate crisis and suggests an effective communication strategy to increase individuals’ eco-friendly actions.